2003
DOI: 10.1259/dmfr/16752462
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of odontogenic myxoma

Abstract: CT clearly demonstrated characteristic features of odontogenic myxoma. CT analysis may contribute to establishing a consensus regarding the interpretation of conventional radiographic appearances in odontogenic myxoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
19
1
2
Order By: Relevance
“…Central odontogenic fibroma is much more collagenized, although there may be focal myxoid areas, and may produce small and scattered deposits of ''dentinoid'', an amorphous, eosinophilic material [5,16]. The case reported here is diffusely myxoid with extensive calcifications.…”
Section: Discussionmentioning
confidence: 67%
“…Central odontogenic fibroma is much more collagenized, although there may be focal myxoid areas, and may produce small and scattered deposits of ''dentinoid'', an amorphous, eosinophilic material [5,16]. The case reported here is diffusely myxoid with extensive calcifications.…”
Section: Discussionmentioning
confidence: 67%
“…4,10,17 These characters explain the aggressive nature of the pathology. Although the borders of 14 (78%) subjects were well defined, 15 (83%) subjects showed an unclear margin in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that these features suggest the invasive nature of the tumour radiographically and advised differentiating from metastatic lesions in the jaw and osteogenic sarcoma. 3,6,11,12 Koseki et al 10 reported that OMs tended to involve the alveolar process in tooth-bearing areas. 5 (33%) of 15 multilocular subjects scalloped between the roots and 9 (60%) subjects interrupted the integrity of alveolar ridge in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tos, dando apariencia de rayos de sol (2,15), lo que no debe ser confundido con reacción perióstica, como se observa en el osteosarcoma. La cortical también puede estar intacta pero adelgazada y expandida, permitiendo la clara identificación de los bordes lesionales (19). Koseki et al (19) usando tomografía computarizada para la evaluación de mixomas, señalan que los tabiques internos no son visibles en todos los casos y que cuando se observan no separan completamente la lesión en múltiples compartimientos.…”
Section: Discussionunclassified